Preschoolers' extension and export of information from realistic and fantastical stories. Issue 4 (21st April 2020) - Weisberg, Deena Skolnick; Hopkins, Emily J.
Abstract: How do young children decide which events can happen within fictional stories (extension) and learn new information from these stories (export)? In two studies, we investigate these two issues as well as the influence of story genre (realistic or fantastical) on these processes. Preschoolers ( N = 192) heard either a realistic or fantastical story and were asked (a) whether a target piece of information should be extended to a different situation within the story context and (b) whether that piece of information could be true in real life. Extension and export were not generally affected by genre, but they were affected by the type of information with which children were presented. Adults ( N = 93) responded similarly. These results suggest that children have a mature tendency to expect stories to remain internally consistent and rely on their background knowledge to interpret story events. Highlights: We tested preschoolers' extension of information within realistic and fantastical stories and their learning from these stories. Children expect stories to remain internally consistent, regardless of genre; both extension and learning were affected primarily by their familiarity with the target material. Children's interactions with stories can shed light on their developing conceptual knowledge.